#TITLE_ALTERNATIVE# - PERDANA GULTOM, PANDU
The case study of this research is APT testing conducted at the Alusan Laboratory of Pusjatan. The APT testing applied to a test pavement structure consisting of two (2) sections of pavement. Both sections of the pavement are divided based on the different of the thickness subbase layers. In this thesis will be discussed how the structural conditions of the two sections, which in the development of more emphasis on the discussion of the condition of section 2 pavement structure test. In the process of development of this research, APT test data used only until loading Ã‚Â± 200,000 passes. The structure of the test pavement is built on indoor facilities, so that the nonexistent water factor and the almost uniform temperature do not have a significant effect. The decrease in the quality of the test pavement structure is greatly influenced by the traffic load applied to it. APT testing is performed after 1 year delay from the time the test structure is completed. It turns out that from the measurement data that the subgrade of the test pavement structure consisting of lime stone improves during 1 year. This causes an increase in strength of the test pavement structure. The model HDM-4 is a predictive model of damage that can be used to predict the initial of damage to a road pavement structure and how its progression. With the prediction model we expected, we can draw up a program of maintenance of a road network. Some damage factors will be modeled such that cracking, ravelling, potholes, edge breaks, rutting, roughness, texture depth, and skid resistance. In this APT test the damage that occurs are rutting, skid resistance, and texture depth. The analysis process is done by analyzing the FWD and MDD deflections required to obtain the existing ITP values, to analyze the ruth depth, then to predict the damage that will occur using the HDM-4 model and to compare it with the actual condition of the test pavement structure. Visually the conditions on the test pavement structure have not shown any significant damage and are generally quite consistent with the HDM-4 model results. For more comprehensive analysis can be done after the loading of the test wheel reaches the design traffic load (750,000 passes).